State Protection Against the Negative Impact of Online Games in Modern Globalization - Prianggodo, Chandra Adjie; Wijayanto, Purbayakti Kusuma (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
Globalization was born as a strong current that flows the transfer of cultural values, products, lifestyles, communication, andtechnology. In this era, the ecosystem of world life has relied on cellphones, computers, and the internet to interact. Onlinegames as a result of advances in science and technology have begun to show a new impact or it can be said that the impact isunpredictable in Indonesia. Some of the impacts of online games are far from positive because they weaken the development ofthe younger generation, including: 1) Relationships with friends and family are tenuous, distant, disharmonious, 2) Decreasedphysical activity that leads to health / fitness / long-term threats. This research method is library research, so the role of theresearcher is dominant to ensure the quality of the research. Researchers strengthen their role by exploring secondary data, sothat data analysis is more credible. The results show that the negative impact of online games is already at a critical level,some cases are (1) murder, (2) health problems, (3) changes in social behavior. In Indonesia, state protection has not yetemerged in anticipating the negative impact of online games. In fact, the state seems to be blundering because it gives legitimacyto the E-Sports ecosystem through the formation of a management institution.Keywords: Protection, Country, Globalization, Online Games